Measurement and identification of aerosols collected near Barrow, Alaska / Motoi Kumai ; prepared for Directorate of Facilities Engineering, Office, Chief of Engineers, by Cold Regions Research and Engineering Laboratory, U.S. Army Corps of Engineers. (1978)
Summary goes here